Sustainable Asset Creation under MGNREGA Scheme in Assam-A Study of Sivasagar and Dhemaji Districts - Saikia, Mrs Mayuri (International Journal of Scientific Research and Management (IJSRM), 2017)
In order to ensure sustained income in the long run leading to improvement in the quality of lives of therural people MGNREGA pointed out a list of nine to create sustainable properties through implementationof the programme in the rural areas. However, the Act also allows creation of personal properties throughthe programme which are more particularly required by the vulnerable sections of the society which weredenied of such benefits so long due to social oppression. Since the inception of MGNREGA, around 252lakh works have been completedthroughout the country as on 31st October 2016 ; of these, almost 51 per cent are works related to water(water conservation, flood control, irrigation, drought proofing, renovation of traditional water bodies andmicro-irrigation), and over 19 per cent works are related to rural connectivity. At such a scale,MGNREGA works have the potential to benefit rural communities by improving irrigation facilities,enhancing land productivity and connecting remote villages to input and output markets